Financial markets and twentieth century industrialization: Evidence from US and Canadian steel producers - Ian Keay; Angela Redish (Queen's University, Department of Economics, 2002)
Despite the diverse and developed nature of twentieth century U.S. and Canadian financial markets, the history of both economies is replete with claims of inefficiency and inadequacy among financial intermediaries, particularly the banking sectors. In Canada it has been argued that banks were oligopolistic and favoured an entrenched merchant class over industrialists. In the U.S. the unit banking system has been perceived as unstable and of an inefficiently small scale. This paper examines the experiences of a set of firms from a large and economically important manufacturing industry; primary steel production; in an effort to determine the impact differences in macro financial markets have had on micro financial decision making. We find statistically significant, but not necessarily economically important, relationships among national capital market characteristics, firms' financing decisions, and firms' capital costs.
Keywords: N42; N62; G32; 330